Cell distrupton, partial purification and product formulation of recombinant bromelain - Muhd. Ezza Faiez bin Othman (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Bromelain is crude, aqueous extract from the stems and fruits of pineapples (Ananascomosus) derived from Bromeliaceae family. In recent advancements in recombinant DNA technology proved to be a promising and effective approach for more sustainable large scale productions of many therapeutic proteins. Nevertheless, since this approach involves expression of proteins in a non-native host microorganism, the overall production processes are not straight-forward due to several common challenges, such as protein degradation during downstream processing steps. As the process, has been subjected to both protein and host-specific, a systematic process conditioning for maximal production of recombinant protein is therefore required. In this research work, the recombinant stem bromelain has been expressed in E.coli BL21-AI (harboring the bromelain gene). Fermented cells were harvested and separated by centrifugation to collect the cell pallets. Cells were then re-suspended in extraction buffer for cell disintegration by continuous ultrasonication. Using Response surface methodology (RSM) based on face-centered central composite design (FCCCD), the optimal conditions for continuous cell disruption by ultrasonication were 13 passes of cycles and 140 ml/min of flow rate. This led to maximum bromelain activity of 0.153 ± 0.001 U/mg-protein. The analysis of variance coupled with value of R2 (0.8547) showed that 85.47% of the model regression. Purification was conducted using ammonium sulphate precipitation. The percentage level of ammonium sulphate saturation was screened initially at 25%, 50%, 75% and 100% (w/v). Confirmation of the percentage saturation was further investigated resulting at 30-40% (w/v) ammonium sulphate saturation yield 80% recombinant bromelain specific activity. Therefore, to maximize the recombinant bromelain activity, bulk precipitation was conducted from 30-60% (w/v) of ammonium sulphate saturation level. For the formulation of the enzyme, five different types of excipients were screened using One factor at a time (OFAT): Arabic Gum, lactose, mannitol, maltodextrin and sucrose. Maltodextrin DE10 was selected due to its capability to have more than 50% specific activity after drying. Further screening was conducted on Maltodextrin DE10 to select the suitable concentration and resulted in 10% Maltodextrin DE10 recovers 50% of the specific activity after spray drying. Optimization of spray drying recombinant bromelain involves three parameters which are inlet temperature (Ti), gas flow height (mm) and feed pump setting (%) were investigated using RSM with FCCD. On statistical analysis, the specified optimum conditions were established having inlet temperature of 126°C, 42mm gas flow height and 12% feed pump settings. This conditions resulted in 0.119 ± 0.0025 U/mg-protein of spray dried recombinant bromelain. Analysis of variance (ANOVA) exhibited greater value of coefficient of determination, R2 (0.9012); suggesting good conformity of 90.12% between the experimental and the theoretical values predicted by the model. In conclusion, the downstream processing of producing the final product of dried powder recombinant bromelain in this study shows the development of the process in obtaining high recovery of the enzyme.